Pembelajaran Pendidikan Agama Islam Dengan Pendekatan Kontekstual Dalam Membentuk Kepribadian Muslim Siswa - Nursyamsu Nursyamsu; Ahmad Sukandar; Asep A. Faturrohman (Jurnal Ilmiah Wahana Pendidikan, 2022)
Through the process of applying competencies in everyday life, students will feel the importance of learning, and they will gain a deep meaning for what they learn. The purpose of this study is to elaborate PAI learning with a contextual approach and its implications for the Muslim personality of students. The research method used is a case study with multi-site research objects, namely MTs N 4 Indramayu, Indramayu district and MTs Darul Falah, Indramayu district. Data analysis is in the form of qualitative analysis and data is collected based on observations, interviews and documentation. The results of the study show that Islamic Religious Education Learning with a contextual approach in shaping the Muslim personality of students, that by carrying out the rules of the teaching and learning system of the Contextual Teaching and Learning (CTL) model can shape the Muslim personality of students. The application of PAI Learning with a Contextual Approach (Contextual Teaching and Learning) in Madrasahs is because; first, the components in the contextual approach are in accordance with the needs of students, second, learning leads to student activity (student oriented), so that students are happier and more enthusiastic in learning, third, the contextual approach is an effective means for teachers in a meaningful and memorable learning process, fourth, contextual learning using a thorough assessment. fifth, the components in the contextual approach are appropriate and very supportive for the realization of the madrasa's vision and mission.